Maternal stress and childhood migraine: a new perspective on management - Esposito M (Dove Medical Press, 2013)
Maria Esposito,1 Beatrice Gallai,2 Lucia Parisi,3 Michele Roccella,3 Rosa Marotta,4 Serena Marianna Lavano,4 Antonella Gritti,5 Giovanni Mazzotta,6 Marco Carotenuto11Center for Childhood Headache, Clinic of Child and Adolescent Neuropsychiatry, Department of Mental Health, Physical, and Preventive Medicine, Second University of Naples, Naples, 2Unit of Child and Adolescent Neuropsychiatry, University of Perugia, Perugia, 3Child Neuropsychiatry, Department of Psychology, University of Palermo, Palermo, 4Department of Psychiatry, "Magna Graecia" University of Catanzaro, Catanzaro, 5Suor Orsola Benincasa University, Naples, 6Unit of Child and Adolescent Neuropsychiatry, Azienda Sanitaria Locale 4, Terni, ItalyBackground: Migraine without aura is a primary headache which is frequent and disabling in the developmental age group. No reports are available concerning the prevalence and impact of migraine in children on the degree of stress experienced by parents. The aim of this study was to evaluate the prevalence of maternal stress in a large pediatric sample of individuals affected by migraine without aura.Methods: The study population consisted of 218 children (112 boys, 106 girls) of mean age 8.32 ± 2.06 (range 6–13) years suffering from migraine without aura and a control group of 405 typical developing children (207 boys, 198 girls) of mean age 8.54 ± 2.47 years. Mothers of children in each group answered the Parent Stress Index-Short Form (PSI-SF) questionnaire to assess parental stress levels.Results: The two groups were matched for age (P = 0.262), gender (P = 0.983), and body mass index adjusted for age (P = 0.106). Mothers of children with migraine without aura reported higher mean PSI-SF scores related to the Parental Distress domain (P < 0.001), Dysfunctional Parent-Child Interaction domain (P < 0.001), Difficult Child subscale (P < 0.001), and Total Stress domain than mothers of controls (P < 0.001). No differences between the two groups were found for Defensive Responding subscale scores.Conclusion: Our study may be the first to highlight the presence of high levels of stress in parents of children affected by migraine without aura.Keywords: parental stress, childhood migraine, migraine without aura, children